Simultaneous Presence of Bacteriochlorophyll and Xanthorhodopsin Genes in a Freshwater Bacterium - Kopejtka, Karel; Tomasch, Jürgen; Zeng, Yonghui; Selyanin, Vadim; Dachev, Marko; Piwosz, Kasia; Tichý, Martin; Bína, David; Gardian, Zdenko; Bunk, Boyke; Brinkmann, Henner; Geffers, Robert; et al. (mSystems, 2020)
Photoheterotrophic bacteria represent an important part of aquatic microbial communities. There exist two fundamentally different light-harvesting systems: bacteriochlorophyll-containing reaction centers or rhodopsins. Here, we report a photoheterotrophic Sphingomonas strain isolated from an oligotrophic lake, which contains complete sets of genes for both rhodopsin-based and bacteriochlorophyll-based phototrophy. Interestingly, the identified genes were not expressed when cultured in liquid organic media. Using reverse transcription quantitative PCR (RT-qPCR), RNA sequencing, and bacteriochlorophyll a quantification, we document that bacteriochlorophyll synthesis was repressed by high concentrations of glucose or galactose in the medium. Coactivation of photosynthesis genes together with genes for TonB-dependent transporters suggests the utilization of light energy for nutrient import. The photosynthetic units were formed by ring-shaped light-harvesting complex 1 and reaction centers with bacteriochlorophyll a and spirilloxanthin as the main light-harvesting pigments. The identified rhodopsin gene belonged to the xanthorhodopsin family, but it lacks salinixanthin antenna. In contrast to bacteriochlorophyll, the expression of xanthorhodopsin remained minimal under all experimental conditions tested. Since the gene was found in the same operon as a histidine kinase, we propose that it might serve as a light sensor. Our results document that photoheterotrophic Sphingomonas bacteria use the energy of light under carbon-limited conditions, while under carbon-replete conditions, they cover all their metabolic needs through oxidative phosphorylation.IMPORTANCE Phototrophic organisms are key components of many natural environments. There exist two main phototrophic groups: species that collect light energy using various kinds of (bacterio)chlorophylls and species that utilize rhodopsins. Here, we present a freshwater bacterium Sphingomonas sp. strain AAP5 which contains genes for both light-harvesting systems. We show that bacteriochlorophyll-based reaction centers are repressed by light and/or glucose. On the other hand, the rhodopsin gene was not expressed significantly under any of the experimental conditions. This may indicate that rhodopsin in Sphingomonas may have other functions not linked to bioenergetics.
Keywords: gene expression; bacteriochlorophyll a; photosynthesis gene cluster; Sphingomonadaceae; aerobic anoxygenic phototrophic bacteria; rhodopsin